2014
DOI: 10.1002/bsl.2136
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Voluntary and Involuntary Readmissions to Forensic Hospitals by Insanity Acquittees in Maryland

Abstract: The current study investigated factors associated with voluntary and involuntary readmissions to forensic hospitals 356 insanity acquittees on conditional release in the state of Maryland from 2007, 2008, and 2009 and monitored their community progress for a 3-year follow-up period. The results indicated that voluntarily readmitted insanity acquittees had fewer reported arrests on conditional release and fewer reported instances of non-compliance with treatment compared with insanity acquittees who were return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Additionally, evaluators did not routinely prioritize those factors that previous research has shown to be most predictive of success or failure on CR. Research has shown that substance abuse treatment, intensive case management, stable housing, and good continuity of care from hospital to community are important factors in differentiating those persons on CR who succeed from those who have their CRs revoked (Marshall et al, 2014; Salem et al, ; Vitacco et al, ). However, evaluators in this study consistently rated these predictive factors lower than most other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, evaluators did not routinely prioritize those factors that previous research has shown to be most predictive of success or failure on CR. Research has shown that substance abuse treatment, intensive case management, stable housing, and good continuity of care from hospital to community are important factors in differentiating those persons on CR who succeed from those who have their CRs revoked (Marshall et al, 2014; Salem et al, ; Vitacco et al, ). However, evaluators in this study consistently rated these predictive factors lower than most other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Vitacco et al () recommend short‐term intensive hospitalizations to reduce rates of CR revocation based on their research with females on CR. Additionally, appropriate housing was found to be a significant predictor of success on CR in both Maryland (Marshall, Reed, & Vitacco, 2014) and Canada (Salem et al, ). Persons on CR who were supervised by officers with specialties in mental health were hospitalized for fewer days as compared with those persons on CR supervised by non‐mental health officers (Gowensmith, Skeem, & McNichols, ).…”
Section: Conditional Release Outcomesmentioning
confidence: 99%
“…The HOM meso-measurements can provide for this much needed evidence based working model to research empirically validated factors to augment our empirical understanding of CR patients as to enhance CR risk assessment and management programmes. Moreover, in line with recommendations of Manguno-Mire et al (2014) and Marshall et al (2014), the HOM model provides for the comparable patient release groups (without follow-up), that are needed to further research the effectiveness of CR. Hence, the HOM meso-measurements provide for the empirical data to enhance and validate treatment effectiveness of CR programmes, to ultimately augment the public safety.…”
Section: Meso-levelmentioning
confidence: 81%
“…This need to research different types of discharge by means of empirically supported methods to provide for a more efficient and effective treatment, is more readily stressed in a recent special issue of Behavioral Sciences and Law (32 (5), 2014) into the practices and outcomes of conditional release (CR) of criminal offenders with mental illness (Vitacco, Green & Felthous, 2014). To complement the lack of consensus in the clinical and legal practice of CR readiness risk assessment and management, these studies focused on (1) assessing risk and improving methodologies for evaluating CR readiness (Crocker, Nicholls, Charette & Seto, 2014;Douglas, 2014;Gowensmith, Bryant & Vitacco, 2014;Green et al, 2014) and (2) success and failure of CR (Manguno-Mire, Coffman, DeLand, Thompson & Myers, 2014;Marshall, Vitacco, Read & Harway, 2014;Novosad, Follansbee, Banfe & Bloom, 2014), to explore and validate empirically based CR related risk and protective factors for the development of standardized assessment protocols. Overall, these studies showed that a number of static and dynamic risk and protective factors were associated with failure and success of CR.…”
Section: Meso-levelmentioning
confidence: 98%
See 1 more Smart Citation